Trends in Psychiatric Emergency Department Visits in Northern Israel During the COVID-19 Outbreak - Pikkel Igal, Yael; Meretyk, Irit; Darawshe, Aziz; Hayek, Samer; Givon, Limor; Levy, Avi; Sipori, Idan; Nuriel, Yonatan; Bloch, Boaz; Buniak, Shraga; Eshel, Ron; Fruchter, Eyal (Frontiers in Psychiatry, 2021)
Background: During the spread of coronavirus disease (COVID-19), mandatory quarantines increased social isolation and anxiety, with inevitable consequences on mental health and health seeking behavior. We wished to estimate those trends. Methods: We examined all psychiatric visits to the emergency department (ED) during March, April 2020, compared to identical months in 2018, 2019. We evaluated both number and nature of referrals. Results: throughout the years, psychiatric referrals comprised about 5% of the total number of ED visits. In March-April 2020, 30% decreases were observed in overall ED visits and in psychiatric referrals in the ED. Compared to 2018-2019, in 2020, the proportions of these diagnoses were higher: anxiety disorders (14.5% vs. 5.4%, p<0.001), personality disorders (6.7% vs. 3.2%, p=0.001), psychosis (9.5% vs. 6.7%, p=0.049), post-traumatic stress disorder (3.2 % vs. 1.5%, p=0.023). Compared to 2018-2019, in 2020, proportions were lower for adjustment disorder (5.8% vs. 8.9%, p=0.036) and for consultation regarding observation (11.7% vs. 31.6%, p<0.001). Differences were not observed between 2018-2019 and 2020 in the proportions of other diagnoses including suicide and self-harm disorders. Referrals concerning suicide and self-harm in a rural hospital and community clinic were 30% lower in the COVID-19 lockdown than in the same months in 2018, 2019. Conclusion: Psychiatric ED visits decreased by the same proportion as overall visits to the ED, apparently driven by fears of COVID-19. Referrals relating suicidality and self-harm shown nominal decrease, but their proportioned share remained constant. Increased anxiety and delayed care may eventually lead to increased mental health needs.